Gawain de Harrison Birtwistle : un opéra (extra-) national ? - Jean-Philippe Heberlé (Revue LISA)
This article deals with Harrison Birtwistle’s opera Gawain (1991). Written on a libretto by the English poet, David Harsent, Gawain is characterized both by national and extra-national elements. The most obvious national features are to be found in the subject of the opera based on the famous English medieval epic poem Sir Gawain and the Green Knight. They are also displayed in the references to Shakespeare, to other British composers (Michael Tippett and Henry Purcell for instance) and to typical English musical or musico-dramatic forms such as the masque. As far as the foreign borrowings or influences are concerned, Harrison Birtwistle’s debt to composers like Richard Wagner, Igor Stravinsky and Olivier Messiaen is once more displayed in Gawain. Other influences are shown through his translation into music of aesthetic ideas inspired by the great German painter Paul Klee and through his adaptation of elements taken from Greek tragedy. One can thus wonder if this fusion or juxtaposition of vernacular and foreign elements is not one of the key features of Gawain.